Peningkatan Hasil Belajar Bahasa Jawa Materi Aksara Jawa Melalui Penggunaan Media Ajar Interaktif Wordwall dan Quizizz pada Peserta Didik Kelas IV Muadz Bin Jabal SD Al-Azhar Syifa Budi Solo - Hanik Khusnul Khotimah; Rifki Ardianto; Riyadi Riyadi; Wafi Anikmah (Universitas Sebelas Maret, 2025)
Javanese language learning in elementary schools plays an important role in preserving local culture, particularly through the introduction of Aksara Jawa (Javanese script) as one of the essential subjects. However, many students still face difficulties in learning the script due to its different characteristics compared to the Latin alphabet. This study aims to improve the learning outcomes of fourth-grade students of Muadz Bin Jabal class at SD Al-Azhar Syifa Budi Solo in the 2024/2025 academic year on the Aksara Jawa material by utilizing interactive media such as Wordwall and Quizizz. The research was conducted using a Classroom Action Research (CAR) approach, which involved two cycles. The data collection techniques used were observation, to examine student engagement and responses, and multiple-choice tests, to evaluate cognitive learning outcomes. The data were analyzed using a descriptive quantitative approach by comparing the pre-cycle test results with the results from each cycle. The results of the study showed a significant increase in scores from the pre-cycle to the second cycle, with the percentage of student mastery in the first cycle reaching 83% and an average score of 80.87, while in the second cycle, student mastery increased to 96% with an average score of 89.13. Therefore, the use of interactive learning media based on technology such as Wordwall and Quizizz has been proven effective in improving students' learning outcomes on the Aksara Jawa material.